Clinical efficacy observation of 4 MHz radiofrequency ablation system in the treatment of anal fistula - Zhu Huiting; Zhang Yang; Zhang Haoyue; Yuan Jiafu; Zhou Hao; Wang Yehuang (结直肠肛门外科)
[Objectives] To observe the clinical efficacy of 4 MHz radiofrequency ablation system in the treatment of anal fistula. [Methods] Sixty patients with intersphincteric or transsphincteric anal fistula who were admitted to the Anorectal Department of Nanjing Hospital of Traditional Chinese Medicine from October 1, 2023 to December 31, 2023 were selected and divided into the observation group (treated with 4 MHz radiofrequency ablation system) and the control group (treated with anal fistulectomy) according to random number table method, with 30 cases in each group. The cure rate, recurrence rate, wound pain intensity (assessed using the Visual Analog Scale, VAS), wound healing time, postoperative complications (including bleeding, incision infection, keyhole deformity, anal edema, urinary retention, and anal distension), and anal function (assessed using the Wexner anal incontinence score) were compared between the two groups. [Results] At 3 months after surgery, the cure rate was 86.7% in the observation group and 93.3% in the control group, with no significant difference (adjusted χ2＝0.185，P＝0.667). At 6 months after surgery, the recurrence rate was 10% in the observation group and 3.3% in the control group, with no significant difference (χ2＝0.268，P＝0.605). The observation group had lower VAS scores for wound pain on the 1st and 7th days after surgery compared to the control group (P<0.05). The wound healing time was (30.6±3.5) days in the observation group and (38.2±4.7) days in the control group, with a statistically significant difference (P<0.05). The total incidence of complications in the observation group was lower than that in the control group P<0.05). There was no statistically significant difference in Wexner anal incontinence score between the two groups before surgery (P>0.05). At 3 months after surgery, the Wexner anal incontinence score of the observation group was lower than that of the control group, (P<0.05). [Conclusion] Compared with anal fistulotomy, the clinical efficacy of the 4 MHz radiofrequency ablation system in treating anal fistula is comparable. It offers advantages in reducing wound pain, accelerating wound healing, decreasing complications such as anal tenesmus and urinary retention, and protecting anal function.